2015
DOI: 10.1016/j.jobcr.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Glucometric assessment of gingival crevicular blood in diabetic and non-diabetic patients: A randomized clinical trial

Abstract: GCB cannot be used for screening blood glucose during periodontal examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 16 publications
1
7
2
Order By: Relevance
“…This shows that gingival crevicular fluid can be used for screening diabetes in a dental office which was in agreement with other studies. [ 12 ] In contrast to our study, other studies[ 25 28 29 ] reported that GCB cannot be used for screening blood glucose during periodontal examination. Diabetes increases inflammation in the periodontal tissues.…”
Section: Discussioncontrasting
confidence: 75%
“…This shows that gingival crevicular fluid can be used for screening diabetes in a dental office which was in agreement with other studies. [ 12 ] In contrast to our study, other studies[ 25 28 29 ] reported that GCB cannot be used for screening blood glucose during periodontal examination. Diabetes increases inflammation in the periodontal tissues.…”
Section: Discussioncontrasting
confidence: 75%
“…The highest and lowest mean values recorded from GCB was 243.27 and 156.07 mg/dl in the DM group and 118.76 and 90.08 mg/dl in the non-DM group respectively [ 12 , 25 35 , 37 , 40 , 41 , 43 45 ]. Two of the studies have found statistically significant differences between GCB and CB values ( p = 0.001) [ 33 , 37 ]. The first study’s mean values for the DM group were 210.56 ± 17.26 mg/dl 178.08 ± 17.66 mg/dl and for the non-DM group 118.76 ± 13.83 mg/dl 86.56 ± 10.17 mg/dl respectively [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two of the studies have found statistically significant differences between GCB and CB values ( p = 0.001) [ 33 , 37 ]. The first study’s mean values for the DM group were 210.56 ± 17.26 mg/dl 178.08 ± 17.66 mg/dl and for the non-DM group 118.76 ± 13.83 mg/dl 86.56 ± 10.17 mg/dl respectively [ 33 ]. The second study reported a mean value of 77.94 ± 38 mg/dl for GCB and 102.96 ± 37 mg/dl for CB [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in accordance with the results of the study carried out by Muller et al and Debnath et al who found significant difference in mean between GCB and FCB values. 16,17 Difference in mean between the two variables indicated that GCB cannot be used as a substitute for FCB for glucose assessment at the same cut-off values.…”
Section: Discussionmentioning
confidence: 99%
“…12 Although most of the past studies support the use of GCB for glucose screening as a non-invasive method but they were conducted on a smaller sample size. [14][15][16][17] Moreover, there is limited literature available to prove the accuracy and reliability of this screening technique and its association with standardized HbA1c test. Therefore, this study was conducted to evaluate if gingival crevicular blood could reliably be used for screening diabetes in patients with periodontitis, with the help of glucometers and to assess the accuracy of this technique as compared to finger capillary blood (FCB) glucose screening and intravenous HbA1c scores.…”
Section: Introductionmentioning
confidence: 99%